Synthesis and Evaluation of Analgesic and Antioxidant Activities of Substituted Benzimidazole Derivatives: Synthesis and Evaluation of Analgesic and Antioxidant Activities - Brishty, Shejuti Rahman; Saha, Poushali; Mahmud, Zobaer Al; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The present study describes the synthesis and pharmacological evaluation of a number of substituted benzimidazole derivatives designated by 3A-1, 3A-2, 3A-3, 3B-1 and 3B-2 through condensation of different o-aryldiamine compounds with the corresponding aldehyde employing ammonium salt as a catalyst. All the compounds were characterized by IR and 1H NMR spectroscopic analysis. The synthesized benzimidazole derivatives were investigated for analgesic and antioxidant activities using acetic acid-induced writhing inhibition in Swiss albino mice and DPPH free radical scavenging assay, respectively. Compounds 3A-3, 3B-1 and 3B-2 at a dose of 50 mg/kg body weight reduced the number of writhings by 88.24%, 84.03% and 85.71%, respectively (p<0.001) in comparison with standard diclofenac (90.76% inhibition). The derivatives 3A-1, 3A-2, 3A-3 and 3B-2 showed prominent antioxidant activity with IC50 values of 0.038, 0.959, 8.834 and 7.519 μg/ml, respectively in comparison with the standard butylated hydroxytoluene (BHT) (14.44 μg/ml). Among the synthesized compounds, 3A-3 and 3B- 2 emerged as the most promising analgesic and antioxidant agents and expressed their potential as lead compounds in future research. Dhaka Univ. J. Pharm. Sci. 19(1): 37-46, 2020 (June)